2014
DOI: 10.1373/clinchem.2013.206805
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Micro Spring Array Device for High-Throughput Enrichment of Viable Circulating Tumor Cells

Abstract: BACKGROUND The dissemination of circulating tumor cells (CTCs) that cause metastases in distant organs accounts for the majority of cancer-related deaths. CTCs have been established as a cancer biomarker of known prognostic value. The enrichment of viable CTCs for ex vivo analysis could further improve cancer diagnosis and guide treatment selection. We designed a new flexible micro spring array (FMSA) device for the enrichment of viable CTCs independent of antigen expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 40 publications
2
109
0
Order By: Relevance
“…In contrast, the membrane filtration can provide size filtration by controlling pore size on the membrane. However, strong shear stress which is applied to cells during the filtration sometimes gives serious damage to cells, or it might give some clotting of cells on the membrane surface222324. Upon comparison of these methods, we can regard our method as an advanced MACS method which can cover size filtration function with maintaining all advantages of conventional MACS method, and our method can overcome all existing problems in conventional membrane filtration method.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the membrane filtration can provide size filtration by controlling pore size on the membrane. However, strong shear stress which is applied to cells during the filtration sometimes gives serious damage to cells, or it might give some clotting of cells on the membrane surface222324. Upon comparison of these methods, we can regard our method as an advanced MACS method which can cover size filtration function with maintaining all advantages of conventional MACS method, and our method can overcome all existing problems in conventional membrane filtration method.…”
Section: Discussionmentioning
confidence: 97%
“…(2) leads to a transfilter pressure of 24 , 32 (10 , 14) Pa, which means that the transfilter pressure of conical holes is one order of magnitude lower than that of 30 mm thick cylindrical-holes. Such a decrease of transfilter pressure can lead to a significant increase of the cell viability [46][47][48][49] , proving again the advantage of conical-hole filters. Moreover, such a small transfilter pressure will remain the same during filtration if the clearance of the filter is efficient.…”
Section: Dp~3mentioning
confidence: 94%
“…Multiple studies using microfiltration for CTC isolation have reported capturing CTC clusters (aka microemboli) (Desitter et al, 2011;Harouaka et al, 2014;Ilie et al, 2014;Vona et al, 2000). These reports indicate that CTC clusters stay intact when isolated with microfiltration methods, whereas other enrichment strategies may either fail to capture clusters or break them apart.…”
Section: Three-dimensional Microfiltration Systemsmentioning
confidence: 99%